Experimental Trypanosoma cruzi Infection Induces Pain in Mice Dependent on Early Spinal Cord Glial Cells and NFκB Activation and Cytokine Production - Borghi, Sergio M.; Fattori, Victor; Carvalho, Thacyana T.; Tatakihara, Vera L. H.; Zaninelli, Tiago H.; Pinho-Ribeiro, Felipe A.; Ferraz, Camila R.; Staurengo-Ferrari, Larissa; Casagrande, Rubia; Pavanelli, Wander R.; Cunha, Fernando Q.; Cunha, Thiago M.; et al. (Frontiers in Immunology, 2021)
The neglected tropical infirmity Chagas disease (CD) presents high mortality. Its etiological agent T. cruzi is transmitted by infected hematophagous insect. Symptoms of acute phase of the infection include fever, fatigue, body aches and headache, making diagnosis difficult, as they are present in other illness as well. Thus, in endemic areas individuals with undetermined pain may be considered for CD. Although pain is a characteristic symptom of CD, its cellular and molecular mechanisms are unknown, except for demonstration of a role for peripheral TNF-α in CD pain. In this study, we evaluated the role of spinal cord glial cells in experimental T. cruzi infection in the context of pain using C57BL/6 mice. Pain, parasitemia, survival, glial and neuronal function as well as NFκB activation and cytokine/chemokine production were assessed. T. cruzi infection induced chronic mechanical and thermal hyperalgesia. Systemic TNF-α and IL-1β peaked 14 days post-infection (p.i.). Infected mice presented increased spinal gliosis and NFκB activation compared to those uninfected mice at 7 days p.i. Glial and NFκB inhibitors limited T. cruzi-induced pain. Nuclear phosphorylated NFκB was detected surrounded by glia markers, and glial inhibitors reduced its detection. T. cruzi-induced spinal cord production of cytokine/chemokine was also diminished by glial inhibitors. DRG neurons presented increased activity in infected mice and the production of inflammatory mediators was counteracted by glial/NFκB inhibitors. The present study unveils the contribution of DRG and spinal cord cellular and molecular events leading to pain in T. cruzi infection, contributing to a better understanding of CD pathology.